Modelling Customer Loyalty in Retail Supermarket Industry Context : Analysis of Perceived Value Perspective in Araz Supermarket - Guliyeva, Aysel (ADA University, 2020)
Nowadays, customers look for getting more value from shopping; negative customer experience could decrease and destroy revenue, that creates a serious business issue for retail stores. According to Gentry and Kalliny (2012), an increase in the number of loyal customers is an opportunity to increase profitability and enhance business sustainability. Hassan (2012) claims that to gain more competitive advantage and market share heavily depends on loyalty. It has not been proved that which features of value customers consider connected and this impacts their loyalty. Theoretically, understanding of value influenced by several independent factors will help business enterprises to increase customer loyalty to the maximum level. For instance, the balance of the following points could be added into successful value propositions: comfortability (Mittal & Gupta, 2012); and place ambiance (Hassan, 2012). This equilibrium would show that some opportunities, which are essential to build customer trips planned to increase primary shoppers and create loyalty, can be missed by supermarket retailers who only use price-cutting to create value. This academic research focuses on the empirical investigation and modelling of customer loyalty in a specific retail supermarket industry of Azerbaijan. Commodity and retail market experienced an exponential growth at the turn of the millennium because the post-Soviet Azerbaijan economy was expanding due to the boost from the oil and gas industry. With more money, more revenue flow into the country, also the influx of foreigners, there was a new demand for diverse goods and commodities that were not normally in supply in the market. Moreover, more of the populations started having more money and can afford luxury and imported goods. Before the Azerbaijan production company developed, the country relied heavily on imported good from foreign countries. Azerbaijan economy is an oil driven and therefore, a lot of the country wealth comes from the oil and gas industry and other supporting industry. Agriculture is ranked second in the country revenue generation (Humbatova, et.al., 2019). In recent years the government through various strategic and policy decisions is making effort to develop other industry with agriculture a huge priority. The government has so far significantly increased state budget towards developing the agriculture sector from a 3,4% of which it was in 2006 (World Bank, 2011) to a significant growth. The government also provides other forms of assistance to famers such as the 10 million AZN lending plan (Azernews, 2018). Not only the government, but also other institutions like the World Bank, the EBRD, EU neighborhood development initiatives, and also the USAID (USAID, 2013) have all contributed to the agriculture sector because they all see the huge potential in the industry and agrees with the government strategic policies. As the current study concentrates on the important sector of retail industry – retail supermarkets, the case study company for this research is Araz Supermarket operating throughout Azerbaijan. Araz is the current market leader and had gained a significant competitive edge against the background of country’s recent economic recovery from a recession stemming from a severe national currency devaluation and import-dependency. However, as the economy is diversifying and the transition to so-called free market economy is becoming a top priority, entry of new market players and the entire competition also grows quite fiercely. Hence, marketers in the retail industry, particularly in grocery and food sectors, are occurred to be rather cautios and delicate with creating the extra value to ‘fasten the bolts’ of brand loyalty to gain a long term growth. Therefore, this academic research takes a deductive look on modelling the loyalty in this specific terrain of business through the lens of perceived customer values and its multiple dimensions.
Keywords: Business; Supermarkets -- Azerbaijan.; Grocery trade -- Azerbaijan.; Customer loyalty programs.; Customer loyalty -- Azerbaijan.